Shape-Evolution and Growth Mechanism of Fe3O4 Polyhedrons - Liqiao Chen; Qiang Zhou; Qingfeng Xiong; Wenlin Li; Jisong Liu; Xianfeng Yang (Advances in Materials Science and Engineering)
The shape evolution of spinel-structured Fe3O4 was systematically investigated using a one-pot solvothermal route. Using FeCl3·6H2O as the precursor, triangular and hexagonal plates, octahedrons, dodecahedrons, and spherical Fe3O4 were obtained by selecting the adequate ration of NaOH, N2H4·H2O, Fe3+, and EDTA. The slow nucleation and growth rate favor the formation of low energy plate-like products, and the spherical crystals are obtained as the result of extremely fast nucleation and growth rate. It is also suggested that the generating rate of Fe(II) reduced from Fe(III) probably affects the growth speed along different facets, further influencing the final size and shape of the produced crystals.